Mice left out in the cold: commentary on the phenotype of TRPM8-nulls - McKemy David D; Daniels Richard L (SAGE Publishing, 2007)
Abstract Detection of innocuous temperatures allows an organism to select an appropriate environmental climate, while the ability to recognize noxious temperature extremes warns of impending tissue damage. For temperatures considered cold, the menthol receptor TRPM8 is activated when temperatures drop below ~26°C, thus making it an intriguing candidate as the molecular mediator of cold perception. However, confirmation of this hypothesis in vivo has eluded researchers until recently. Three independent research groups have reported that mice lacking this single gene are severely impaired in their ability to detect cold temperatures. Remarkably, these animals are deficient in many diverse aspects of cold signaling, including cool and noxious cold perception, injury-evoked sensitization to cold, and cooling-induced analgesia. These animals provide a great deal of insight into the molecular signaling pathways that participate in the detection of cold and painful stimuli.